Composite fiscal decentralisation and green innovation: Imperative strategy for institutional reforms and sustainable development in OECD countries. (11th February 2022) - Sun, Yunpeng; Razzaq, Asif
Abstract: Improving environmental quality and fiscal management has become one of the utmost imperative policy agendas for sustainable development. Although many studies explore multiple deriving factors of environmental sustainability; however, very little is known regarding the impact of composite (revenue and expenditure) fiscal decentralisation (FD) on environmental quality. Manifestly, the intergovernmental fiscal relations advocate to ensure the alignment of tax and spending powers to promote sustainable and inclusive growth. Therefore, we explore the asymmetric linkages between composite FD, green innovation, institutional governance and carbon emissions in 32 OECD countries. Our preliminary results confirm non‐linearity and structural changes in data, which instigate us to apply the asymmetric method of moments quantile regression. The overall findings exhibit that composite FD significantly mitigates carbon emissions only at medium to higher (5th–9th) emissions quantiles. In contrast, green innovation reduces carbon emissions from lower to medium (1st–5th) emissions quantiles. Institutional reforms promote environmental sustainability across all emissions quantiles (1st–9th). Interestingly, the emissions‐reducing effect of composite FD, green innovation and institutional governance is highest for higher emissions quantiles and lowest for lower emissions quantiles. These results provide valuable policy recommendations for all stakeholders.